2018
DOI: 10.1002/ccr3.1644
|View full text |Cite
|
Sign up to set email alerts
|

A case of antithyroid drug‐induced agranulocytosis from a second antithyroid drugs (ATD) administration in a relapsed Graves' disease patient who was tolerant to the first ATD treatment

Abstract: Key Clinical MessageAgranulocytosis is a rare side effect of antithyroid drugs (ATD) that usually develops within the first 3‐6 months after starting treatment. We present a 64‐year‐old patient who developed agranulocytosis after starting ATD to treat relapsed Graves' disease. This patient had tolerated the first course of ATD for 72 months. This was an unusual case in which a serious side effect developed during a second ATD course. It is essential that clinicians remain vigilant to the fact that antithyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The best prevention is to educate patients when prescribing antithyroid drugs. Robinson et al reported that 60.9% of patients were not aware of the symptoms of agranulocytosis and 30% of these patients after investigation, found the fact that patients did not receive an explanation of agranulocytosis so that they experienced delays in diagnosis which could result in an increased risk of mortality (6,17,18).…”
Section: Preventionmentioning
confidence: 99%
“…The best prevention is to educate patients when prescribing antithyroid drugs. Robinson et al reported that 60.9% of patients were not aware of the symptoms of agranulocytosis and 30% of these patients after investigation, found the fact that patients did not receive an explanation of agranulocytosis so that they experienced delays in diagnosis which could result in an increased risk of mortality (6,17,18).…”
Section: Preventionmentioning
confidence: 99%
“…Conversely, other studies have found that thionamide-induced neutropenia is independent of dose, age, duration of treatment, or second exposure to the drug [9] Patients with Grave's disease may occasionally course with neutropenia before initiating treatment wit h tionamides, due to the unpredictable and idiosyncratic nature; for this reason, most experts recommend monitoring the blood count [10] It is important to educate the patient about this complication, and is instructed to discontinue the drug, if he has fever and sore throat. The prognosis of drug-induced neutropenia has improved with advances in supportive therapy, including antibiotics, blood transfusions, and the use of granulocytic colony-stimulating factor (GM-CSF) [11].…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…According to literatures, we summarize the antithyroid arthritis syndrome as [1] a patient was diagnosed hyperthyroidism; [2]who developed arthritis after treating with antithyroid drugs; [3] who noted the typical symptom of migratory multi-joint pain, [4]occurred within 2-3 months secondary to the use of antithyroid drugs; [5] the symptoms resolved shortly or relieved after discontinuing drug; [6] No joint deformities remain; [7]No past history of arthritis4-6. Given that the present case developed arthritis 1 month after the patient started receiving methiamazole, we diagnosed Antithyroid arthritis syndrome.…”
Section: Case Reportmentioning
confidence: 99%